ELECTRONIC MEDICAL RECORDS AS DIGITAL TRANSFORMATION IN INDONESIAN HEALTH SERVICES 4.0 - Mayasafira, Sarrah Dwiananda; Almansoob, Mohammed (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
The application of Electronic Medical Record in the era of Digital Transformation Indonesia 4.0 is the main pillar in revolutionizing health services. EMR presents a fundamental shift in medical information management by replacing traditional medical records with integrated electronic forms. Thus, this makes quickly access and share patient data, improve coordination between providers, and inform more accurate clinical decision making. This study aims to systematically review the implementation Digital Transformation in Indonesian as a planning to achieve Health Services 4.0. This study implements systematic reviews using Preferred Reporting Systematic Reviews and Meta-analysis (PRISMA) approach. Research articles published from google scholar, PubMed and sagepub. To take appropriate and relevant article research, relevant keywords or terms are constructed as the following words: Digital transformation OR digital revolution OR digital 4.0; Health services OR health care OR Health facilities; Digital medical records. 30 articles were collected from: Google Scholar, PubMed and Sagepub. The quality of these articles was evaluated, resulting in 7 articles being synthesized in the final literature review report.The results show that EMR analyzes in-depth data, supports the development of evidence-based health policies, and personalizes care according to patient characteristics. The adoption of EMR also presents challenges, including data security and privacy protection where cybersecurity and regulatory compliance are critical.